Sports Orthopedics - Hönning A; Stengel D; Güthoff C (Deutsche Zeitschrift für Sportmedizin)
In the MiSpEx project, the statistical analysis of main research questions accompanied by the aggregation of diverse data obtained in the individual studies represents a particular challenge. Research goals relating to the effectiveness and efficiency of training interventions in order to reduce the risk and degree of back pain may be addressed by meta-analyticalapproaches. This requires a sufficient similarity of the underlying studies and, in case of applying a meta-analysis of individual data,uniformly structured data sets. Approaches of supervised statistical learning should be applied to research goals concerning the diagnosis of back pain, and the prognosis either of further course of symptoms and of the reaction to preventive and curative interventions. The various underlying data sets should enable a step-by-step approach with several development and validation steps, likewise provided that sufficient comparability exists. The assessment of moderating effects of the influencing factors pain experience, training status, psychophysical distress, and level of care on treatment success is of high importance.KEY WORDS: Aggregation, Analysis Strategy, Prevention, Back Pain